Technology stocks and economic performance of government-linked companies: the case of Malaysia - Wong, Chan-Yuan; Govindaraju, V. G. R. Chandran (Technological and Economic Development of Economy, 2012)
On the basis of the case study of the selected government-linked companies (GLCs), this paper examines the technological stock progress and further assesses its implication for growth. A synthesized framework of analysis (using technological stock and logistic growth function) is proposed to highlight the virtuous cycle between R&D investment, technology stock and growth. The results suggest that two of the selected firms (Proton and Golden Hope), indeed, showed better technological progress. However, Proton seems to achieve the maturity stage of technology and further needs to enhance its technology capability to drive its performance in the future. In contrast, TNB is found to lack the technological development to promote performance. The results, on the one hand, suggest that technology development is mostly progressive with high returns in the areas where the country has definite comparative advantage (e.g. oil palm) and when better partnership exists. On the other hand, in a highly protective market, the technological progress is slow – the case of energy sector – and contribution of technology progress towards growth is in lack – as in the case of automotive sector. Case comparison suggests that attempts to develop technology require competitive market with less government protective measures.